Zaginięcie przedsiębiorcy a działalność przedsiębiorstwa — zarys problemu - Wójcik, Paweł (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
This article provides an outline of the analysis of problems caused by the disappear-ance of an entrepreneur in the context of his business. The purpose of the publication is to draw attention to the previously overlooked aspect of the disappearance of a natural person conducting business activities. The disappearance of an entrepreneur raises a number of separate problems not only in the personal sphere, but above all in the property sphere of the entrepreneur, his employees, contractors, or clients. The author of this article has analyzed the legal consequences of an entrepreneur’s disappearance in the context of his business. Then he identified the legal institutions im-plemented by the legislator, which can be used to avoid, or at least mitigate the negative effects of the said disappearance, and made their practical analysis in relation to the case of disappearance of an entrepreneur actively conducting business activities. This analysis was the basis for proposing a comprehensive solution through the joint use of several legal institutions operating in the legal regime to obtain the most effective protection of business participants in the event of the disappearance of an entrepreneur. Finally, he as-sessed the functioning legal institutions and proposed in which direction the legislator’s further actions should be taken to regulate the increasingly important problem of the disappearance of a participant of business trading. The aforementioned analysis led the author to the conclusion that the disappearance does not cause the entrepreneur’s non-existence to be recognized, and thus has virtually no legal effect on the property of the enterprise. In view of the above, despite the fact that the missing entrepreneur does not actually run the enterprise, during his unavoidable absence, his liabilities become chargeable, in particular property liabilities, in the public and private sphere, which may lead to the squandering of his assets, and at the same time to the violation of the interests of third parties related to the process of doing business. While the application of several legal institutions may limit the harmful effects of an entrepreneur’s disappearance on his property sphere and third parties, including those involved in business transactions, the legal solutions possible to apply in the event of an entrepreneur having gone missing should be evaluated negatively. In particular, none of them alone fully solves the problem of securing an enterprise in the event of disappearance, and most solutions are simply unreal in the event of an entrepreneur having gone missing. In practical terms, highlighting the problem of an entrepreneur’s disappearance from the point of view of its legal effects and the possibility of removing its negative consequences will increase its rank in the assessment of search institutions and may con-tribute to the development of new solutions. It should be postulated that regardless of the analyzed solutions, the legislator plans and introduces mechanisms independent of the will of a missing entrepreneur, which would be applicable in the event of the disappearance of an entrepreneur by law, and allow immediate protection of his assets during his search. The above would make it pos-sible to respond to the growing needs of society in this respect.
Keywords: przedsiębiorcy; zaginięcie przedsiębiorcy; przedsiębiorstwo a zaginiony przedsiębiorca; działalność gospodarcza po zaginięciu przedsiębiorcy; majątek zaginionego przedsiębiorcy